Studies on in vitro response to callus induction and gene transfer technique of five high yielding indica rice varieties. - Khan, Md. Niuz Morshed; Islam, Dr. Md. Monirul; Islam, Dr. Md. Shahidul (Journal of Scientific Agriculture, 2019)
Due to growing population, there is an increasing demand of rice production but the productivity of rice is lessened day by day. To overcome this problem various biotechnological tools can be used for developing various rice varieties. However, the lack of a simple and efficient protocol for callus induction, embryogenic callus formation and quick plant regeneration in this cereal crop. In this study embryogenic calli from mature seeds of five indica rice varieties viz. Binadhan-5, Binadhan-6, BRRI dhan-48, BRRI dhan-58 and IR-64were observed that is done in four different concentration of growth regulators (2,4-D). The highest callus induction were observed in media containing 2 mg/L 2,4-D. Among those varieties BRRI dhan-48 showed highest rate of callus induction. In this experiment Agrobacterium mediated gene transfer is also tried although plants were found nut need to be tested by molecular methods and tested the desired characters for selecting those plantlets as transgenic plant. This study will be useful for selecting suitable callus induction medium for callus induction in future.